Advances in Quality of Life Theory and Research
XI, 267 p.
Keywords: The International Society for Quality of Life Studies held its first conference in Charlotte, North Carolina in 1997. Participants at the conference were allowed to submit their papers for the present volume. The submitted manuscripts went through a review and revision process, and the papers in this book represent the best articles from that process. Because the society sponsoring this volume is international in character, it is not sur prising that the 11 contributions are from 4 different countries: Canada (3), India (1), Netherlands (3), and the United States (4). Thus, the volume is cross-national in authorship, although we hope that future works can include more papers from additional nations. Ten of the eleven papers consider quality of life in terms of some aspect of subjective well-being. The book is broken into three sections: the first section presenting material on broad theories of subjective well being, the second section covering how work and income are related to subjective well-being, and the third section containing one chapter on health and one on political representation. I am proud to present these broad-ranging chapters on quality of life.